2022
DOI: 10.1002/jgc4.1609
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing for genetic counseling: A unified framework for persuasive and equipoise conversations

Abstract: Genetic counselors (GCs) have traditionally been trained to adopt a position of equipoise or clinical neutrality. They provide information, answer questions, address barriers, and engage in shared decision‐making, but generally, they do not prescribe a genetic test. Historically, GCs have generally been trained not to persuade the ambivalent or resistant patient. More recently, however, there has been discussion regarding when a greater degree of persuasion or directionality may be appropriate within genetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The category of Guidance has implications for the long‐standing discussions in the field about the appropriate use of a spectrum of directiveness. The conversation has evolved beyond the tenet of non‐directiveness to a goal of increasing patient autonomy (Kessler, 1992) and using techniques, such as shared decision making (Elwyn et al, 2000; Shugar & Shuman, 2020) and motivational interviewing (Resnicow et al, 2022), to aid clients in making informed decisions that improve their health and the health of their families while incorporating their own personal values. Such techniques are compatible with the range of guidance identified in our study, which found many examples of genetic counselors providing guidance, ranging from subtle language to strongly worded health promotion (for example, see Table 2 in sections on Guidance as Strategy and as Purpose).…”
Section: Discussionmentioning
confidence: 99%
“…The category of Guidance has implications for the long‐standing discussions in the field about the appropriate use of a spectrum of directiveness. The conversation has evolved beyond the tenet of non‐directiveness to a goal of increasing patient autonomy (Kessler, 1992) and using techniques, such as shared decision making (Elwyn et al, 2000; Shugar & Shuman, 2020) and motivational interviewing (Resnicow et al, 2022), to aid clients in making informed decisions that improve their health and the health of their families while incorporating their own personal values. Such techniques are compatible with the range of guidance identified in our study, which found many examples of genetic counselors providing guidance, ranging from subtle language to strongly worded health promotion (for example, see Table 2 in sections on Guidance as Strategy and as Purpose).…”
Section: Discussionmentioning
confidence: 99%
“…While goal-oriented and directional, MI is autonomy supportive rather than directive (Resnicow et al, 2022).…”
Section: Use Of Cyoa To Practice Motivational Interviewing Skills In ...mentioning
confidence: 99%
“…The widely accepted, short definition of MI is a collaborative, person‐centered form of guiding to elicit and strengthen motivation for change (Miller & Rollnick, 2012). While goal‐oriented and directional, MI is autonomy supportive rather than directive (Resnicow et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While genetic counseling encompasses a risk communication component, it should extend beyond this information to provide personalized psychotherapeutic support counseling that may more effectively influence behavior [21]. It has been shown that genetic counseling, under these conditions, leads to an increased sense of perceived personal control and greater intention of engaging in positive health behaviors [22, 23].…”
Section: Introductionmentioning
confidence: 99%